Sm-Fe-N rare earth magnet, its manufacturing method, and rare earth magnet powder

JP7651465B2Active Publication Date: 2025-03-26TDK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021553676
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-29
Filing Date
2020-10-29
Publication Date
2025-03-26
Estimated Expiration
2040-10-29

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、残留磁束密度及び保磁力が向上したSm-Fe-N系希土類磁石及びその製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651465000001
    Figure 0007651465000001
  • Figure 0007651465000002
    Figure 0007651465000002
  • Figure 0007651465000003
    Figure 0007651465000003
Patent Text Reader

Abstract

This Sm-Fe-N rare earth magnet contains Sm-Fe-N crystal grains. The oxygen content in the Sm-Fe-N rare earth magnet is 0.5 mass% or less based on the total amount of the Sm-Fe-N rare earth magnet, and the average grain size of the Sm-Fe-N crystal grains is 1 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Sm-Fe-N rare earth magnet, a method for producing the same, and rare earth magnet powder. [Background technology]

[0002] Since Sm-Fe-N rare earth magnets have a high Curie temperature and exhibit magnetic properties equivalent to those of Nd-Fe-B magnets, they are being improved as magnets with excellent heat resistance. For example, Patent Document 1 discloses a method for producing an Sm-Fe-N magnet compact, in which Sm-Fe-N magnet powder at a predetermined temperature is compacted at a predetermined compacting surface pressure to obtain an Sm-Fe-N magnet compact having a predetermined relative density.

[0003] Furthermore, Patent Document 2 discloses a sintered magnet which includes a crystal phase consisting of a plurality of Sm-Fe-N crystal grains and a nonmagnetic metal phase present between adjacent Sm-Fe-N crystal grains, and in which the ratio of the SmFeN peak intensity to the Fe peak intensity measured by X-ray diffraction is within a predetermined range.

[0004] Furthermore, Non-Patent Document 1 discloses that a coarse powder containing Sm-Fe-N crystal grains with a reduced oxygen content is prepared, the coarse powder is wet-pulverized to prepare an alloy powder, and the alloy powder is sintered by plasma sintering to obtain a sintered magnet. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 198396 [Patent Document 2] International Publication No. 2018 / 163967 [Non-patent literature]

[0006] [Non-Patent Document 1] M. Matsuura et al., J. Magn. Magn. Mater., 467, 64 (2018). Summary of the Invention [Problem to be solved by the invention]

[0007] Generally, the residual magnetic flux density (Br) and coercive force (HcJ) are used as indicators of the magnetic properties of Sm-Fe-N rare earth magnets. However, there is room for improvement in the residual magnetic flux density and coercive force of the Sm-Fe-N magnet compact obtained by the method disclosed in Patent Document 1, as well as the sintered magnets disclosed in Patent Document 2 and Non-Patent Document 1.

[0008] The present invention has been made in view of the above circumstances, and has an object to provide an Sm-Fe-N rare earth magnet with improved residual magnetic flux density and coercive force, a method for producing the same, and rare earth magnet powder used therein. [Means for solving the problem]

[0009] One aspect of the present invention relates to an Sm-Fe-N rare earth magnet containing Sm-Fe-N crystal grains, in which the oxygen content in the Sm-Fe-N rare earth magnet is 0.5 mass % or less based on the total amount of the Sm-Fe-N rare earth magnet, and the average grain size of the Sm-Fe-N crystal grains is 1 μm or less.

[0010] Here, the carbon content in the Sm-Fe-N rare earth magnet may be more than 0.05 mass % and not more than 1.0 mass % based on the total amount of the Sm-Fe-N rare earth magnet.

[0011] Furthermore, the rare earth magnet does not need to include a non-magnetic metal phase.

[0012] Furthermore, the total amount of non-magnetic metals contained in the metal phase other than the Sm-Fe-N crystal grains (excluding the non-magnetic metals contained in the oxide phase) may be 0.05 mass % or less with respect to the entire rare earth magnet.

[0013] One aspect of the present invention is Sm-Fe-N-based rare earth magnet powder containing Sm-Fe-N-based crystal grains, wherein the oxygen content in the Sm-Fe-N-based rare earth magnet powder is 0.5% by mass or less based on the total amount of the Sm-Fe-N-based rare earth magnet powder, the average particle size of the Sm-Fe-N-based crystal grains is 1 μm or less, and the carbon content in the Sm-Fe-N-based rare earth magnet powder is more than 0.1% by mass and 4.5% by mass or less based on the total amount of the Sm-Fe-N-based rare earth magnet powder.

[0014] Another aspect of the present invention is a method for manufacturing an Sm-Fe-N-based rare earth magnet containing Sm-Fe-N-based crystal grains, the method including a step of degassing and dehydrating a liquid, a pulverization step of pulverizing Sm-Fe-N-based alloy coarse powder in the degassed and dehydrated liquid to obtain fine powder, a step of forming the fine powder in a magnetic field to obtain a formed body, and a step of sintering the formed body.

[0015] Here, the oxygen content of the fine powder can be 0.5% by mass or less, the average particle size of the fine powder can be 1 μm or less, and the carbon content in the fine powder can be more than 0.1% by mass and 4.5% by mass or less.

Advantages of the Invention

[0016] According to the present invention, there are provided an Sm-Fe-N-based rare earth magnet with improved residual magnetic flux density and coercive force, and a method for manufacturing the same.

Embodiments for Carrying Out the Invention

[0017] Hereinafter, preferred embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0018] <Sm-Fe-N-based Rare Earth Magnet> The rare earth magnet according to this embodiment is an Sm-Fe-N rare earth magnet containing Sm-Fe-N crystal grains, in which the oxygen content in the rare earth magnet is 0.5 mass% or less based on the total amount of the rare earth magnet, and the average grain size of the crystal grains is 1 μm or less.

[0019] Sm-Fe-N crystal grains are crystal grains of an alloy containing Sm, Fe, and N. Examples of the crystal structure of Sm-Fe-N crystal grains include TbCu7 type crystals and Th2Zn 17 Among them, Th2Zn 17 Sm-Fe-N crystal grains having a Th2Zn type crystal structure are preferred. 17 An example of a type crystal is SmFe 17 N x The symbol x is 1 to 6, preferably 2 to 4, more preferably 2.5 to 3.5, and further preferably 2.8 to 3.2, and can be 3.

[0020] The SmFe in the cross section parallel to the c-axis of the rare earth magnet according to this embodiment 17 The area ratio of N3 crystal grains is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more.

[0021] The average grain size of the Sm-Fe-N crystal grains is 1 μm or less, and since this further improves the residual magnetic flux density and coercive force of the rare earth magnet, it is preferably 0.7 μm or less, and more preferably 0.5 μm or less. There is no lower limit to the average grain size, but it can be, for example, 0.1 μm or 0.04 μm.

[0022] The average grain size of the Sm-Fe-N crystal grains can be measured based on an SEM image of a cross section parallel to the c-axis of the sintered magnet. That is, based on the image, the cross-sectional area of ​​each of 500 Sm-Fe-N crystal grains is determined by image analysis, and each area is converted into the diameter of a circle having the same area (diameter equivalent to area circle) to obtain the grain size distribution of the Sm-Fe-N crystal grains. The median diameter (D50) of the resulting number-based grain size distribution is obtained and used as the average grain size of the Sm-Fe-N crystal grains.

[0023] The rare earth magnet according to this embodiment may have a metal phase other than Sm-Fe-N crystal grains. Such a metal phase may be, for example, an Fe phase. The area ratio of such a metal phase in a cross section parallel to the c-axis is preferably 10% or less, and more preferably 5% or less.

[0024] It is preferable that the rare earth magnet does not include a nonmagnetic metal phase. The nonmagnetic metal phase is a metal phase that contains a larger amount of nonmagnetic metal in terms of atomic percentage than the main phase (Sm-Fe-N crystal grains). Since Sm-Fe-N crystal grains usually contain 8 to 10 atomic %, i.e., 20 to 25 mass %, of Sm, which is a nonmagnetic metal, it is particularly preferable that the rare earth magnet does not include a nonmagnetic metal phase that contains 10 mass % or more of nonmagnetic metal. The nonmagnetic metal is a metal other than a ferromagnetic metal (e.g., Fe, Co, Ni, etc.), and examples of such metal include Zn, Al, Sn, Cu, Ti, Sm, Mo, Ru, Ta, W, Ce, La, V, Mu, and Zr. In addition, the rare earth magnet may have a total amount of nonmagnetic metal (excluding nonmagnetic metal contained in oxide phase) contained in a metal phase other than the main phase (Sm-Fe-N crystal grains), such as a grain boundary phase, of 0.05 mass % or less of the entire rare earth magnet. Even if the rare earth magnet does not contain a non-magnetic metal phase, it may contain an oxide phase of the non-magnetic metal.

[0025] The oxygen content in the rare earth magnet according to this embodiment is 0.5% by mass or less based on the total amount of the rare earth magnet, and is preferably 0.45% by mass or less because this further improves the residual magnetic flux density and coercive force. The oxygen content in the rare earth magnet can be measured by melting the rare earth magnet in a graphite crucible in an inert gas atmosphere, reacting the oxygen in the rare earth magnet with the carbon in the graphite crucible to generate CO, and detecting the amount of CO by spectroscopic measurement using a non-dispersive infrared detector or the like.

[0026] The oxygen in the rare earth sintered magnet can exist in the grain boundary phase and / or the oxide phase.

[0027] The rare earth magnet according to this embodiment may further contain at least one element selected from the group consisting of C, Al, Si, P, Ti, Cr, Mn, Co, Cu, Zn, Y, Zr, Sn, and W, in addition to Sm, Fe, and N. The content of elements other than Sm, Fe, and N is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0028] The carbon content in the rare earth magnet according to this embodiment is preferably more than 0.05% by mass and not more than 1.0% by mass based on the total amount of the rare earth magnet. The carbon content in the rare earth magnet can be 0.2% by mass or more and 0.6% by mass or less. At least a portion of the carbon can be present in the grain boundary phase.

[0029] The amount of carbon in a rare earth magnet can be obtained by crushing the rare earth magnet in an agate mortar in an inert atmosphere glove box to obtain powder, combusting the powder in an oxygen stream to convert it into CO, and quantifying the CO in the combustion gas by infrared absorption spectrometry.

[0030] The composition of the rare earth magnet according to this embodiment may be determined by analytical methods such as energy dispersive X-ray spectroscopy (EDS), X-ray fluorescence (XRF) analysis, inductively coupled plasma (ICP) optical emission spectrometry, inert gas fusion-non-dispersive infrared absorption spectrometry, oxygen flow combustion-infrared absorption spectrometry, and inert gas fusion-thermal conductivity spectrometry.

[0031] The residual magnetic flux density Br of the rare earth magnet according to this embodiment is preferably 10.5 kG or more, more preferably 10.7 kG or more, and even more preferably 11.0 kG or more. The residual magnetic flux density of the rare earth magnet can be measured using a VSM (vibrating sample magnetometer) or a BH tracer.

[0032] The coercivity Hcj of the rare earth magnet according to this embodiment is preferably 10.3 kOe or more, more preferably 10.5 kOe or more, and still more preferably 11.0 kOe or more. The coercivity of the rare earth magnet means a value measured using a VSM (sample vibration magnetometer) or a B-H tracer.

[0033] The dimensions and shape of the rare earth magnet according to this embodiment vary according to the use of the rare earth magnet and are not particularly limited. The shape of the permanent magnet may be, for example, a rectangular parallelepiped, a cube, a rectangle (plate), a polygonal prism, an arc segment, a fan, an annular sector, a sphere, a disc, a cylinder, a ring, or a capsule. The shape of the cross section of the rare earth magnet may be, for example, a polygon, an arc (circular chord), an arcuate shape, an arch, or a circle.

[0034] The rare earth magnet according to this embodiment may be used in various fields such as hybrid vehicles, electric vehicles, hard disk drives, magnetic resonance imaging devices (MRI), smartphones, digital cameras, thin TVs, scanners, air conditioners, heat pumps, refrigerators, vacuum cleaners, washing and drying machines, elevators, and wind power generators. The rare earth magnet may be used as a material constituting a motor, a generator, or an actuator.

[0035] <Manufacturing method of Sm-Fe-N based rare earth magnet> An example of the manufacturing method of the Sm-Fe-N based rare earth magnet (hereinafter also referred to as "rare earth magnet") according to this embodiment will be described.

[0036] [Sm-Fe-N based coarse powder preparation step]

[0037] (Sm-Fe-N based alloy coarse powder) First, prepare an Sm-Fe-N based alloy coarse powder. Sm2Fe 17 N xCoarse powder of Sm-Fe-N alloy such as alloy is available on the market, and its manufacturing method is also known. For example, Sm-Fe-N alloy coarse powder can be obtained by nitriding alloy coarse powder containing Sm and Fe (hereinafter also referred to as "Sm-Fe alloy"). Sm-Fe alloy may be manufactured by, for example, calcium reduction diffusion method or casting method.

[0038] The average particle size of the Sm-Fe-N alloy coarse powder may be 5 to 50 μm, and more preferably 10 to 30 μm. The average particle size is D50 of the particle size distribution based on the number of particles measured by the laser diffraction method.

[0039] The oxygen content of the coarse alloy powder is preferably 0.5 mass % or less, and more preferably 0.3 mass % or less.

[0040] [Crushing process] Next, the above Sm-Fe-N alloy coarse powder is pulverized (wet pulverized) in liquid (solvent) to obtain alloy fine powder (Sm-Fe-N rare earth magnet powder).

[0041] In this embodiment, the remanence and coercivity of the resulting rare earth magnet can be improved by pulverizing the Sm-Fe-N alloy coarse powder in a degassed and dehydrated liquid (solvent) to obtain alloy fine powder. The reason why such an effect is achieved is not clear, but it is thought to be as follows. That is, by performing wet pulverization in which the alloy coarse powder is pulverized in a liquid (solvent), the average particle size of the alloy fine powder can be made smaller than when dry pulverization is performed. If the average particle size of the alloy fine powder is small, the coercivity of the rare earth magnet after sintering is improved. Here, when the alloy coarse powder is pulverized in a liquid (solvent) that has not been subjected to any treatment, the water and oxygen dissolved in the liquid (solvent) react with Fe on the surface of the alloy coarse powder / fine powder, and FeO and Fe2O3 are generated on the surface of the alloy fine powder. When the alloy fine powder with FeO and Fe2O3 generated on the surface is sintered, FeO and Fe2O3 are reduced by Sm contained in the alloy fine powder to become Fe. Fe is soft magnetic and serves as the starting point for magnetization reversal, which reduces the residual magnetic flux density and coercive force of the resulting rare earth magnet. Therefore, by grinding the coarse alloy powder in a degassed and dehydrated liquid (solvent), it is believed that the oxidation of the surface of the resulting fine alloy powder is suppressed, improving the residual magnetic flux density and coercive force of the resulting rare earth magnet.

[0042] The liquid (solvent) contains an organic solvent and may further contain a dispersant as necessary. It is preferable that the liquid does not contain phosphoric acid.

[0043] In particular, when wet grinding is carried out in a liquid containing an organic solvent (a solvent containing carbon atoms) or in a liquid containing an organic solvent and an organic dispersant, the organic solvent and / or organic dispersant adheres (e.g., physically or chemically adsorbed) to the surface of the alloy fine powder after grinding, making it easy to introduce carbon atoms into the rare earth magnet after sintering, particularly into the grain boundaries.

[0044] The amount of carbon atoms in the sintered rare earth magnet can be adjusted as appropriate by controlling the amounts of the organic solvent and organic dispersant, the amount of carbon atoms in the molecules of the organic solvent and organic dispersant, the boiling points / melting points of the organic solvent and organic dispersant, the grinding conditions, and the sintering conditions.

[0045] For example, the greater the proportion of carbon in the organic solvent and organic dispersant molecules, the greater the tendency for the amount of carbon in the alloy powder and the sintered rare earth magnet to increase. The proportion of carbon in the organic solvent molecules is preferably 80% by mass or more. The proportion of carbon in the organic dispersant molecules is preferably 60% by mass or more.

[0046] The higher the melting point or boiling point of the organic solvent and organic dispersant, the less likely they are to volatilize due to the energy consumed during grinding or sintering, making it easier to increase the amount of carbon in the sintered rare earth magnet.

[0047] The boiling point of the organic solvent is preferably 100° C. or higher. The organic dispersant is preferably a liquid at room temperature and has a melting point of 10° C. or higher.

[0048] A smaller proportion of oxygen in the organic solvent and organic dispersant molecules is preferable because this can suppress the reaction between Sm-Fe-N crystal grains and oxygen during grinding and sintering, thereby suppressing the formation of oxides and metallic Fe phases.

[0049] The organic solvent is preferably one that does not have a hydroxyl group, since it is easy to reduce the dissolved oxygen concentration and water concentration. As such an organic solvent, for example, saturated hydrocarbons such as pentane, hexane, heptane, octane, cyclohexane, and cycloheptane, unsaturated hydrocarbons such as pentene, hexene, heptene, cyclopentene, cyclohexene, cycloheptene, 4-methylcyclohexene, and 1-methylcyclohexene, and aromatic hydrocarbons such as benzene, toluene, and xylene can be used. The organic solvent may be used alone or in combination of two or more kinds. The hydrocarbon may be linear, cyclic, or structural isomer.

[0050] The organic solvent may be a compound containing elements other than carbon and hydrogen. Examples of such solvents include alcohols such as methanol, ethanol, butanol, propanol, hexanol, benzyl alcohol, ethylene glycol, propylene glycol, and glycerin; ethers such as diethyl ether, tetrahydrofuran, and dioxane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone ketone; esters such as methyl acetate, ethyl acetate, and butyl acetate; nitrile compounds such as acetonitrile; dimethylformamide; and dimethyl sulfoxide.

[0051] The liquid may contain a combination of any two or more of the organic solvents listed above.

[0052] Examples of organic dispersants may be fatty acids or derivatives of fatty acids. Examples of organic dispersants are, for example, oleic acid, oleylamine, and octylamine.

[0053] Other examples of organic dispersants include butyric acid, caproic acid, caprylic acid, capric acid, lauric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, caprylamine, laurylamine, stearylamine, oleylamine, ethylenediamine, aniline, pyridine, and other surfactants. The liquid may contain any combination of two or more of the above dispersants.

[0054] By using the above liquid for wet grinding, it is possible to obtain alloy fine powder with a carbon-containing compound attached to the surface, and carbon can be present at the grain boundaries of the sintered rare earth magnet. In contrast, even if carbon is present in the crystals of the alloy fine powder used as the raw material, it is difficult to precipitate carbon at the grain boundaries of the sintered rare earth magnet.

[0055] (Degassing and dehydration of liquid (solvent)) The degassing treatment is not particularly limited as long as it is a method capable of reducing the dissolved oxygen concentration in the liquid (solvent), and examples thereof include a method of bubbling an inert gas in the liquid (solvent), a method of freezing and degassing the liquid (solvent), and a method of contacting the liquid (solvent) with an oxygen adsorbent. When the degassing treatment is a method of bubbling an inert gas, the bubbling time and the amount of inert gas supplied to the liquid (solvent) may be appropriately changed depending on the target dissolved oxygen concentration in the liquid (solvent) after the degassing treatment. Examples of the inert gas are nitrogen and argon, and nitrogen is preferred.

[0056] The dissolved oxygen concentration in the liquid (solvent) after degassing is preferably 1 ppm or less, and more preferably 0.1 ppm or less, since this further improves the remanence and coercivity of the resulting rare earth magnet. In this specification, the dissolved oxygen concentration of the liquid (solvent) is a value measured with a dissolved oxygen meter, and means the mass ratio of oxygen to the total mass of the liquid (solvent).

[0057] The dehydration treatment of the liquid (solvent) is not particularly limited as long as it is a method capable of reducing the water concentration in the liquid (solvent), and examples thereof include a method using a desiccant, etc. Such desiccant is not particularly limited as long as it is capable of removing water in the liquid (solvent), and examples thereof include molecular sieves, etc.

[0058] The water concentration in the liquid (solvent) after the dehydration treatment is preferably 10 ppm or less, and more preferably 1 ppm or less, in order to further improve the remanence and coercivity of the resulting rare earth magnet. In this specification, the water concentration of the liquid (solvent) is a value measured by the Karl Fischer method, and means the mass ratio of water to the total mass of the liquid (solvent).

[0059] The degassing and dehydration treatments of the liquid (solvent) may be performed simultaneously, or one treatment may be performed first and then the other treatment. When the liquid (solvent) contains an additive such as a dispersant in addition to the organic solvent, each component of the liquid (solvent) before mixing may be degassed and dehydrated, and then the components may be mixed to obtain the liquid (solvent), or the liquid (solvent) after mixing may be degassed and dehydrated.

[0060] In the pulverization step, for example, a pulverization method such as a ball mill, a vibration mill, or a mixer mill may be used. The pulverization step is preferably carried out in an inert gas atmosphere, since this further improves the residual magnetic flux density and coercive force of the resulting rare earth magnet. In particular, an inert gas atmosphere with an oxygen concentration of 10 ppm or less is preferred. The oxygen concentration here is expressed as a volume fraction. The time for which the pulverization step is carried out may be appropriately changed depending on the target average particle size of the alloy fine powder.

[0061] The average particle size of the alloy fine powder at the end of the pulverization process is preferably 1 μm or less, more preferably 0.7 μm or less, in order to further improve the coercive force of the rare earth magnet. The average particle size of the alloy fine powder is determined using an observation image of the alloy fine powder by SEM. Specifically, the area of ​​500 alloy fine powder particles is determined based on the observation image by image analysis, and the area of ​​each fine powder is converted into the diameter of a circle having the same area (diameter equivalent to an area circle) to obtain the particle size distribution of the alloy fine powder. The D50 of the obtained number-based particle size distribution is taken as the average particle size of the alloy fine powder. There is no lower limit to the average particle size of the alloy fine powder, but it can be, for example, 0.1 μm or 0.04 μm. The alloy fine powder can be substantially a single crystal of an alloy containing Sm, Fe, and N (Sm-Fe-N alloy), and the average particle size of the crystal grains of the sintered magnet can be adjusted based on the average particle size of the fine powder. If the average particle size of the alloy fine powder exceeds 1 μm, the surface area becomes small, the surface adsorption of compounds containing carbon becomes insufficient, and the effect of suppressing the generation of compounds such as samarium oxide, iron oxide, and metallic iron during the sintering process tends to be insufficient.

[0062] The oxygen content of the alloy fine powder is preferably 0.5% by mass or less, and more preferably 0.4% by mass or less, based on the total amount of the alloy fine powder, in order to further improve the residual magnetic flux density and coercive force of the resulting rare earth magnet. If the oxygen content in the alloy fine powder is high, compounds such as samarium oxide, iron oxide and metallic iron are more likely to be generated and grow due to thermal decomposition and lattice distortion during the sintering process, and these phases become the starting points for magnetization reversal in the main phase particles, causing a decrease in coercive force.

[0063] The carbon content of the alloy fine powder is not particularly limited, but is preferably more than 0.1 mass% and not more than 4.5 mass% based on the total amount of the alloy fine powder. The lower limit of the carbon content may be 0.2 mass% or 0.4 mass%.

[0064] Compounds other than the organic solvent and the organic dispersant may be present on the surface of the alloy fine powder, but it is preferable that the amount of compounds containing O is small.

[0065] On the other hand, if there is sufficient carbon on the surface of the alloy powder, the formation of compounds such as samarium oxide, iron oxide, and metallic iron during the sintering process is suppressed. This suppresses the formation of magnetization reversal origins, physically and magnetically separates the main phase particles, and is believed to improve the magnetic properties of the sintered magnet. On the other hand, if there is too much carbon on the surface of the alloy powder, C will replace N inside the Sm-Fe-N crystal grains, and there is a tendency for Sm-Fe-C or Sm-Fe-CN to be formed in excess. Sm-Fe-C and Sm-Fe-CN are phases with lower magnetic properties than Sm-Fe-N, and the remanence and coercivity of the sintered magnet will decrease.

[0066] By sintering fine alloy powder with low oxygen content, small particle size, and a carbon content within a specified range, a Sm-Fe-N rare earth magnet with excellent magnetic properties can be obtained.

[0067] The oxygen content and carbon content of the alloy powder can be measured in the same manner as for the rare earth magnet (sintered magnet).

[0068] [Molding process] Next, the alloy powder is molded in a magnetic field to obtain a compact. When molded in a static magnetic field, a compact is obtained in which the magnetization easy axis of the alloy particles is oriented along the static magnetic field, and an anisotropic magnet is obtained after sintering, which is preferable. For example, the alloy powder is pressed with a die while applying a static magnetic field to the alloy powder in the die to obtain a compact. The pressure exerted by the die on the alloy powder may be 10 MPa or more and 3000 MPa or less. The strength of the magnetic field applied to the alloy powder may be 400 kA / m or more and 3000 kA / m or less.

[0069] [Sintering process] Next, the above-mentioned molded body is sintered to obtain a sintered magnet. The sintering conditions may be appropriately set depending on the composition of the target rare earth magnet and the average particle size of the alloy fine powder. The sintering process may include a temperature increase process and a temperature holding process following the temperature increase process, or may include only the temperature increase process. The temperature reached in the temperature increase process may be, for example, 150°C or higher and 600°C or lower. The sintering time in the temperature holding process may be 5 hours or less, or may be 0 hours.

[0070] The heating method for sintering is not particularly limited, and may be resistance heating, electrical heating, or high-frequency heating. Heating may also be performed while applying pressure to the green compact / sintered compact in a mold.

[0071] The oxygen concentration and moisture concentration in the atmosphere during the sintering step are each preferably 1 ppm or less, and more preferably 0.5 ppm or less, where the oxygen concentration and moisture concentration in the atmosphere are expressed as molar fractions.

[0072] [Cooling process] The sintered body is then cooled. The sintered body may be cooled in an inert gas. The cooling rate of the sintered body may be, for example, 5° C. / min to 100° C. / min.

[0073] It is preferable that the steps from the Sm-Fe-N coarse powder preparation step to the sintering step be carried out in an inert gas atmosphere such as nitrogen.

[0074] [Processing process] If necessary, the method may further include a processing step of adjusting the size and shape of the obtained sintered magnet by cutting, polishing, etc. The processing step is also preferably carried out in an inert gas atmosphere. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0076] Example 1 [Crushing process] 500 g of n-octane (organic solvent) and 10 g of oleic acid (organic dispersant) were prepared. Next, n-octane and oleic acid were mixed to obtain a liquid (solvent), and then nitrogen bubbling was performed in the liquid (solvent) for 3 hours to degas the liquid (solvent). Next, 200 g of molecular sieves 3A was added to the liquid (solvent) and left for 1 hour to dehydrate the liquid (solvent).

[0077] As alloy coarse powder, Sm2Fe 17 N x (x≒3, average particle size D 50 The oxygen content of the alloy coarse powder was 0.25 mass %, and the carbon content was less than 0.01 mass %. The alloy coarse powder was wet-pulverized in a mixer mill using zirconia beads (manufactured by Nikkato, product name: YTZ balls) in the presence of the liquid (solvent) after deaeration and dehydration to obtain alloy fine powder. The wet-pulverization was carried out in a nitrogen atmosphere with an oxygen concentration of 5 ppm until the average particle size of the alloy fine powder reached the value shown in Table 1.

[0078] [Molding process] The obtained alloy powder was fed into a die. A static magnetic field was applied to the alloy powder in the die while the alloy powder was compressed with the die to obtain a compact. The pressure applied to the alloy powder was 1.2 GPa, and the strength of the static magnetic field applied was 2500 kA / m.

[0079] [Sintering process] The obtained molded body was heated to 500°C in a nitrogen atmosphere while pressing the die at 1.2 GPa, and allowed to cool after reaching 500°C to obtain a sintered magnet. The oxygen concentration in the nitrogen atmosphere in the sintering step was the value shown in Table 1. The oxygen concentration was measured using a zirconia type oxygen concentration meter. All the above steps were carried out in a nitrogen atmosphere.

[0080] Example 2 A sintered magnet of Example 2 was obtained in the same manner as Example 1, except that the oxygen concentration in the nitrogen atmosphere in the sintering step was changed to the value shown in Table 1.

[0081] (Examples 3 and 4) Sintered magnets of Examples 3 and 4 were obtained in the same manner as in Examples 1 and 2, except that the wet-pulverization time was increased and the process was continued until the average particle size of the fine alloy powder after the pulverization process reached the value shown in Table 1.

[0082] (Comparative Examples 1 to 6) The sintered magnets of Comparative Examples 1 to 6 were obtained in the same manner as in Example 1, except that dry grinding was performed in a nitrogen atmosphere using a jet mill instead of wet grinding in a mixer mill. The average particle size of the alloy fine powder after dry grinding in each Comparative Example and the oxygen concentration in the nitrogen atmosphere during the sintering step were the values ​​shown in Table 1. The combination of the dry grinding time and the oxygen concentration during sintering was changed from one Comparative Example to another.

[0083] (Comparative Examples 7 to 14) The sintered magnets of Comparative Examples 7 to 14 were obtained in the same manner as in Example 1, except that acetonitrile was used instead of n-octane as the organic solvent, no dispersant was used, and the liquid (solvent) was not degassed or dehydrated. The combination of the wet-milling time and the oxygen concentration during sintering was changed in each Comparative Example. The average particle size of the alloy fine powder after wet-milling and the oxygen concentration in the nitrogen atmosphere during the sintering process in each Comparative Example were the values ​​shown in Table 1.

[0084] (Comparative Examples 15 to 18) Except for the degassing and dehydration treatment of the liquid, the same procedures were followed as in Comparative Examples 7 to 10. The average particle size of the alloy fine powder after wet pulverization in each Comparative Example and the oxygen concentration in the nitrogen atmosphere in the sintering step were set to the values ​​shown in Table 1 to obtain the sintered magnets of Comparative Examples 15 to 18.

[0085] (Example 101) A sintered magnet of Example 101 was obtained in the same manner as in Example 1, except that acetonitrile was used instead of n-octane as the organic solvent and no dispersant was used.

[0086] (Examples 102 and 103) Sintered magnets of Examples 102 and 103 were obtained in the same manner as in Example 1, except that caprylic acid and lauric acid, in that order, were used as the organic dispersant instead of oleic acid.

[0087] (Example 104) A sintered magnet of Example 104 was obtained in the same manner as in Example 1, except that n-dodecane was used instead of n-octane as the organic solvent, and stearic acid was used instead of oleic acid as the organic dispersant.

[0088] (Examples 105 to 108) The sintered magnets of Examples 105 to 108 were obtained in the same manner as in Examples 101 to 104, except that the oxygen concentration during sintering was 0.5 ppm.

[0089] (Examples 109 to 112) The sintered magnets of Examples 109 to 112 were obtained in the same manner as in Examples 101 to 104, except that the wet-pulverization time was increased to reduce the particle size.

[0090] (Examples 113 to 116) The sintered magnets of Examples 113 to 116 were obtained in the same manner as in Examples 109 to 112, except that the oxygen concentration during sintering was 0.5 ppm.

[0091] (Example 117) A sintered magnet of Example 117 was obtained in the same manner as in Example 3, except that octadecane was used instead of n-octane as the organic solvent, and stearic acid was used instead of oleic acid as the organic dispersant.

[0092] (Example 118) A sintered magnet of Example 118 was obtained in the same manner as in Example 4, except that octadecane was used instead of n-octane as the organic solvent, and stearic acid was used instead of oleic acid as the organic dispersant.

[0093] (Comparative Example 101) A sintered magnet of Comparative Example 101 was obtained in the same manner as in Example 103, except that the liquid after addition of the dispersant was not degassed or dehydrated, and the wet-pulverization time was shortened to increase the particle size.

[0094] (Comparative Example 102) A sintered magnet of Comparative Example 102 was obtained in the same manner as in Comparative Example 101, except that the oxygen concentration during sintering was 0.5 ppm.

[0095] (Comparative Examples 103 to 108) Sintered magnets of Comparative Examples 103 to 108 were obtained in the same manner as in Comparative Examples 101 and 102, except that the wet-pulverization time was changed to successively decrease the particle size.

[0096] (Comparative Examples 109 to 112) The sintered magnets of Comparative Examples 109 to 112 were obtained in the same manner as in Comparative Examples 101 to 104, except that the liquid after the addition of the dispersant was degassed and dehydrated.

[0097] (Comparative Examples 113 to 124) The sintered magnets of Comparative Examples 113 to 124 were obtained in the same manner as in Comparative Examples 101 to 112, except that the organic dispersant was oleic acid.

[0098] Tables 1 to 3 show the carbon mass percentages in the organic solvent molecules and the boiling points, and the carbon mass percentages in the organic solvent molecules and the melting points used.

[0099] Tables 1 to 3 show the type of organic solvent, the carbon mass fraction in the organic solvent molecule, the boiling point of the organic solvent, the type of organic dispersant, the carbon mass fraction in the organic dispersant, and the melting point of the organic dispersant.

[0100] [Measurement of the average particle size of the alloy fine powder after crushing] The average particle size of the alloy fine powder was determined using images of the alloy fine powder observed with a SEM (manufactured by Hitachi High-Technologies Corporation, product name: "SU5000"). Specifically, the area of ​​500 alloy fine powder particles was determined by image analysis based on the observed images, and the area of ​​each particle was converted into the diameter of a circle having the same area (diameter equivalent to an area circle) to measure the particle size distribution of the alloy fine powder. The D50 of the measured number-based particle size distribution was taken as the average particle size of the alloy fine powder. The results are shown in Tables 1 to 3.

[0101] [SmFe in sintered magnets 17 Measurement of the average grain size of N3 crystal grains Sm2Fe in sintered magnets 17 The average grain size of the N3 crystal grains was measured using a TEM (manufactured by FEI Company, product name: "Titan") observation image of a cross section parallel to the c-axis. 17 The area of ​​N3 crystal grains was obtained by image analysis, and each area was converted into the diameter of a circle having the same area (area-equivalent circle diameter). 17 The grain size distribution of N3 crystal grains was obtained. The D50 of the obtained grain size distribution based on the number of grains was calculated as 17 The average grain size of N3 crystal grains was determined. The results are shown in Tables 4 to 6.

[0102] [Measurement of oxygen content in alloy powders and sintered magnets] The oxygen content of the coarse alloy powder, the fine alloy powder, and the sintered magnet was measured using a metal oxygen analyzer. Specifically, the coarse alloy powder, the fine alloy powder, and the sintered magnet were melted in a graphite crucible to gasify the oxygen in the fine alloy powder (to CO), and the CO was detected and quantified using a non-dispersive infrared detector. The results are shown in Tables 1 to 6.

[0103] [Measurement of carbon content in alloy powders and sintered magnets] The carbon contents of the alloy coarse powder, the alloy fine powder, and the sintered magnet were obtained by crushing each sample in an agate mortar in an inert atmosphere glove box to obtain powder, combusting the powder in an oxygen stream to convert it into CO, and quantifying the CO in the combustion gas by infrared absorption method. The results are shown in Tables 1 to 6.

[0104] Observation by EDS confirmed that the sintered magnets of the examples did not have a non-magnetic metal phase, and that at least a portion of carbon was present in the grain boundary phase. It was also confirmed that the alloy fine powders of the examples had a solvent and / or dispersant attached to the alloy surface. In the sintered magnets of the examples, the total amount of non-magnetic metals contained in metal phases other than the Sm-Fe-N crystal grains (excluding non-magnetic metals contained in the oxide phase) was 0.05 mass% or less of the entire rare earth magnet.

[0105] [Magnetic property measurement] The magnetic properties of the alloy powder and sintered magnets were measured using a VSM. The magnetic properties measured were remanence (Br), coercivity (HcJ), remanence (Jr), and saturation magnetic polarization (Js). The degree of orientation (Jr / Js) was also calculated. The Br of the alloy powder was calculated as mass magnetization Mr (emu / g). The results are shown in Tables 1 to 6.

[0106] [Calculating relative density] The dimensions and mass of the resulting sintered magnets were measured, revealing that the SmFe 17 The relative density of the sintered magnet to the true density of the N3 crystal was calculated, and the results are shown in Tables 1 to 6.

[0107] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6]

[0108] It has been confirmed that the sintered magnets of the examples, which have an oxygen content of 0.5 mass % or less and an average grain size of Sm-Fe-N crystal grains of 1 μm or less, can achieve both high residual magnetic flux density (e.g., 10 kG or more) and high coercive force (e.g., 10 kOe or more).

[0109] Furthermore, it was confirmed that when the carbon content of the sintered magnet is more than 0.05 mass % and not more than 1.0 mass %, it is possible to achieve both a higher residual magnetic flux density and a higher coercive force.

[0110] It was also confirmed that the use of Sm-Fe-N rare earth magnet powder having an oxygen content of 0.5 mass% or less, an average particle size of 1 μm or less, and a carbon content of more than 0.1 mass% and not more than 4.5 mass% makes it easier to produce sintered magnets that combine residual magnetic flux density and coercive force.

Claims

1. A Sm-Fe-N rare earth sintered magnet containing Sm-Fe-N crystal grains, the oxygen content in the Sm—Fe—N rare earth sintered magnet is 0.5 mass % or less based on the total amount of the Sm—Fe—N rare earth sintered magnet, The average grain size of the Sm—Fe—N crystal grains is 1 μm or less, The carbon content in the Sm-Fe-N rare earth sintered magnet is more than 0.05 mass % and not more than 1.0 mass % based on the total amount of the Sm-Fe-N rare earth sintered magnet, and at least a portion of the carbon is present in a grain boundary phase.

2. 2. The Sm-Fe-N rare earth sintered magnet according to claim 1, which is free of a non-magnetic metal phase.

3. 3. The Sm—Fe—N rare earth sintered magnet according to claim 1, wherein the total amount of nonmagnetic metals contained in metal phases other than Sm—Fe—N crystal grains (excluding nonmagnetic metals contained in oxide phases) is 0.05 mass% or less with respect to the entire rare earth sintered magnet.

4. A Sm-Fe-N rare earth sintered magnet described in any one of claims 1 to 3, wherein the carbon content in the Sm-Fe-N rare earth sintered magnet is greater than 0.05 mass% and not more than 0.6 mass%, based on the total amount of the Sm-Fe-N rare earth sintered magnet.

5. A Sm-Fe-N rare earth sintered magnet described in any one of claims 1 to 3, wherein the carbon content in the Sm-Fe-N rare earth sintered magnet is 0.2 to 0.6 mass% based on the total amount of the Sm-Fe-N rare earth sintered magnet.

6. A Sm-Fe-N rare earth magnet powder containing Sm-Fe-N crystal grains, the oxygen content in the Sm—Fe—N rare earth magnet powder is 0.5 mass % or less based on the total amount of the Sm—Fe—N rare earth magnet powder; The average grain size of the Sm—Fe—N crystal grains is 1 μm or less, The Sm-Fe-N rare earth magnet powder has a carbon content of more than 0.2 mass % and not more than 4.5 mass % based on the total amount of the Sm-Fe-N rare earth magnet powder, and a carbon-containing compound is adhered to the surface of the magnet powder.

7. A method for producing a Sm—Fe—N rare earth sintered magnet containing Sm—Fe—N crystal grains, comprising the steps of: Degassing and dehydrating the liquid; a grinding step of grinding the Sm—Fe—N alloy coarse powder in the deaerated and dehydrated liquid to obtain a fine powder; A step of compacting the fine powder in a magnetic field to obtain a compact; and and sintering the molded body. The oxygen content of the fine powder is 0.5% by mass or less, The fine powder has an average particle size of 1 μm or less, The carbon content in the fine powder is more than 0.2 mass% and not more than 4.5 mass%, The method of claim 1, wherein a carbon-containing compound is adhered to the surface of said fine powder.

Citation Information

Patent Citations

  • Magnetic material and its manufacture

    JP1996045718A

  • Manufacture of magnet

    JP1998163056A

  • Rotating machine

    JP2001230111A

  • Isotropic compound, isotropic bonded magnet, rotating machine, and magnet roll

    JP2001313205A

  • Sm-Fe-N MAGNETIC PARTICLE POWDER, ITS MANUFACTURING METHOD, AND BOND MAGNET

    JP2006283094A